The making of a Black scholar : from Georgia to the Ivy League - Porter, Horace A., 1950- (Singular lives., 2003)
This captivating and illuminating book is a memoir of a young black man moving from rural Georgia to life as a student and teacher in the Ivy League as well as a history of the changes in American education that developed in response to the civil rights movement, the war in Vietnam, and affirmative action. Born in 1950, Horace Porter starts out in rural Georgia in a house that has neither electricity nor running water. In 1968, he leaves his home in Columbus, Georgia - thanks to an academic scholarship to Amherst College - and lands in an upper-class, mainly white world.